1989
DOI: 10.1016/0042-6989(89)90178-8
|View full text |Cite
|
Sign up to set email alerts
|

The relative numbers of long-wavelength-sensitive to middle-wavelength-sensitive cones in the human fovea centralis

Abstract: Abstrset-The determination of the relative numbers of different cone types in the human retina is fundamental to our understanding of visual sensitivity and color vision; yet direct measurements which provide this basic information have not previously been made for ail cone types. Here we present a model which links the detection of a test light of small dimension to the number of cones contributing to detecfon of the light. We selectively isolated either the long-wavelength-sensitive (L) or the middle-wavelen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
96
2
2

Year Published

1989
1989
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(113 citation statements)
references
References 21 publications
13
96
2
2
Order By: Relevance
“…Determinations of the best-fitting theoretical functions (Cicerone & Nerger, 1989 and as described below) for our measurements were made by a least-squares method ("zxssqz" subroutine from the IMSL Mathematical Library).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Determinations of the best-fitting theoretical functions (Cicerone & Nerger, 1989 and as described below) for our measurements were made by a least-squares method ("zxssqz" subroutine from the IMSL Mathematical Library).…”
Section: Methodsmentioning
confidence: 99%
“…The results for these dichromats were compared to those of six color normal trichromatic observers whose results have been presented in detail elsewhere (Cicerone & Nerger, 1985 The remaining two dichromats (LH and KG) and two trichromat (VV and HA) were mildly myopic and optical corrections were applied for these observers.…”
Section: Observersmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, fine isoluminant chromatic patterns can appear as luminance and chromatic spatial noise (Sekiguchi et al, 1993). Another example is that subjects routinely misjudge the color appearance of tiny flashes of monochromatic light (Holmgren, 1884;Hartridge, 1954;Krauskopf, 1964Krauskopf, , 1978Cicerone and Nerger, 1989;Hofer et al, 2005).…”
Section: Implications Of L/m Cone Arrangement For Visionmentioning
confidence: 99%
“…Whereas the short-wavelength-sensitive-(S) cone submosaic has been relatively well characterized (Williams et al, 1981;de Monasterio et al, 1985;Ahnelt et al, 1987;Curcio et al, 1991), the organization of long-wavelength-sensitive (L) and middle-wavelength-sensitive (M) cones in the human retina has proven more elusive, because they exhibit no known morphological or histochemical differences and their pigments are 96% identical (Nathans et al, 1986). Several studies using indirect measurements have suggested that there are on average more L cones than M cones, with large intersubject variability (DeVries, 1946;Rushton and Baker, 1964;Cicerone and Nerger, 1989;Pokorny et al, 1991;Yamaguchi et al, 1997;Hagstrom et al, 1998;Brainard et al, 1999;Deeb et al, 2000;Kremers et al, 2000;Otake and Cicerone, 2000;Carroll et al, 2002). A limitation of these estimates is that they often involve the untested assumption that each M cone and each L cone contribute equally to the molecular, physiological, or psychophysical mechanisms being monitored to derive L:M ratio estimates.…”
Section: Introductionmentioning
confidence: 99%